Anti-epidermal growth factor receptor monoclonal antibodies in metastatic colorectal cancer: A meta-analysis - Song, Qi-Bin (World J Gastroenterol, 2015)
AIM: To investigate the correlation between Kirsten rat sarcoma viral oncogene homolog (KRAS) status and the therapeutic effects of anti-epidermal growth factor receptor (EGFR) monoclonal antibodies (MoAbs) in metastatic colorectal cancer (mCRC). METHODS: Randomized controlled trials (RCTs) were identified and the association between KRAS mutation and clinical outcome in mCRC patients treated with anti-EGFR MoAbs was investigated. Ten RCTs were included in this meta-analysis. Progression-free survival and overall survival were used to assess the strength of the relationship between KRAS mutation and clinical outcome. RESULTS: In first-line treatment, survival benefit was confined to patients with wild-type KRAS. Chemotherapy regimens and angiogenesis inhibitor treatment influenced the results of the analysis. Wild-type KRAS mCRC patients did not seem to benefit from oxaliplatin-based chemotherapy (PFS: HR = 0.88, 95%CI: 0.70-1.10; OS: HR = 0.93, 95%CI: 0.82-1.04). Clinical benefit in mCRC patients was limited to therapeutic regimens which included anti-EGFR MoAbs and fluorouracil-based therapy (PFS: HR = 0.77, 95%CI: 0.69-0.86; OS: HR = 0.85, 95%CI: 0.75-0.95). When anti-EGFR MoAbs were used as second- or further-line treatment, clinical benefit was still confined to patients with wild-type KRAS. CONCLUSION: KRAS status is a potential predictive marker of clinical benefit due to anti-EGFR MoAb therapy in mCRC patients.